Histopathology of Fusarium wilt of staghorn sumac (Rhus typhina) caused by Fusarium oxysporum f. sp. callistephi race 3. III. Host cell and tissue reactions - Ouellette, Guillemond; Cherif, Mohamed; Simard, Marie (Phytoprotection)

(untitled) (Société de protection des plantes du Québec, 2006)
AbstractVarious cell reactions occurred in staghorn sumac plants inoculated with Fusarium oxysporum f. sp. callistephi. Light and transmission electron microscopy observations and results of cytochemical tests showed: 1) increased laticifers and latex production in the phloem; 2) tylosis formation; 3) host cell wall modifications, including appositions or other cell wall thickenings; and 4) unusual cross wall formation in some cells, and cell hypertrophy and hyperplasia. Tylosis walls labelled for pectin and cellulose and many displayed inner suberin-like layers. These layers were also noted in cells of the medullary sheath and in many cells with dense content and thickened walls in the barrier zones that had formed. These zones also contained fibres with newly-formed gelatinous-like layers. In the vicinity of these cells, host cell walls were frequently altered, associated with opaque matter. Many small particles present in chains also occurred in some of these cells, which contained only remnants of host cytoplasm. Light microscopy observations showed that pronounced tissue proliferation and aberrant cells occurred in the outer xylem in the infected plants. Unusual neoplasmic tissue also formed from cells surrounding the pith and medullary sheath, and it spanned directly across the pre-existing xylem tissue and burst as large mounds on the stems.